If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -60 + 40x = 20x Solving -60 + 40x = 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. -60 + 40x + -20x = 20x + -20x Combine like terms: 40x + -20x = 20x -60 + 20x = 20x + -20x Combine like terms: 20x + -20x = 0 -60 + 20x = 0 Add '60' to each side of the equation. -60 + 60 + 20x = 0 + 60 Combine like terms: -60 + 60 = 0 0 + 20x = 0 + 60 20x = 0 + 60 Combine like terms: 0 + 60 = 60 20x = 60 Divide each side by '20'. x = 3 Simplifying x = 3
| (t)+2.7=4.5 | | -7(y-2)=-2y+39 | | 6(k-7)-(8+9k)=-4k | | 8n-3(5)= | | x^2+4x=5x | | -2x+21=7x-15 | | 8(2x-4)+5(3x+6)=29 | | (2x+28)(4x+10)= | | -3x+1=-2(3x+10) | | 2w^2+2w=34 | | 5r+15=2.25r | | 3(6+x)=30 | | 3x+4-2-x=14 | | -3(e+4)=4w-5 | | -3+2x=-x-6 | | 1-6x=5-4x | | 22-44= | | 13x+9=-15 | | 2a+4.2=3a-16 | | 2y+4=26 | | XY=98 | | 12p=-4 | | -6n+7n+4= | | 5k+8(k-4)=-84 | | 4x-7=x-34 | | 5y-5=7y+9+10y+4 | | -11=1+8k | | k*(-9k)*k=0 | | X(3x-5)=(3x+8)(x-5) | | 3+2(3n+2)=41 | | 11x+13(19-x)=211 | | -9t(t-2)=4(t-15) |